Methodological and scientific support for student sports teams - Koroleva, O. Yu.; Alekseeva, A. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimed at confirming the effectiveness of the psychological support provided to the women's volleyball team by the coaching staff to improve the performance of the game.